Master Wars / Raja Adleina Marsya Raja Azman Shah - Raja Azman Shah, Raja Adleina Marsya (Universiti Teknologi MARA, Kedah, 2018)
Master Wars is a 2D fighting game, which characters who are chefs that fights using their unique abilities and weapon to fight. Characters are from various countries who uses kitchen utensils, from their respective countries that they represent, as weapons to fight one another.